The Globalization of Ayahuasca Shamanism and the Erasure of Indigenous Shamanism. (September 2016) - Fotiou, Evgenia
Abstract: Ayahuasca is a hallucinogenic plant mixture used in a ceremonial context throughout western Amazonia, and its use has expanded globally in recent decades. As part of this expansion, ayahuasca has become popular among westerners who travel to the Peruvian Amazon in increasing numbers to experience its reportedly healing and transformative effects. Drawing from ethnographic fieldwork in and around the area of Iquitos, Peru, the epicenter of ayahuasca tourism, this paper focuses on some of the problematic aspects of western engagement with indigenous spiritual traditions. This engagement is usually based on idealized and romanticized notions of indigenous shamanism and an inability to digest its less palatable aspects, such as sorcery. Through ethnographic examples and ethnohistorical evidence, I show that the romanticization indigenous peoples is not benign. In fact, this one‐sided romantic image hides the complexity of indigenous peoples' situations by erasing the injustices that they have experienced and continue to experience. I propose a more holistic approach to ayahuasca shamanism that views indigenous peoples not living in a fictitious harmony with nature but as people embedded in larger struggles and facing important challenges not the least of which is the recent commercialization of indigenous spirituality.